The role of oxidation treatments before and after CVD synthesis of graphene on copper catalytic surface - Neuvonen, Santeri (2021)
Graphene is a sheet of honeycomb bonded carbon, that is only one atom thick. Aside from its remarkable strength, graphene has great conducting and photochemical prop erties. Due to its unique properties, it can be used as viable option for rare metals in circuits and in new type of measuring components. To express these properties at their best, graphene should be single crystal and as clean as possible. In this bachelor thesis, different treatment options for catalytic metal surface for graphene synthesis are studied in chemical vapor deposition growth. Different options to treat the catalytic metal layer were studied, such as changes in gas compositions in annealing process, electropolishing, plasma and UV-light treatment. All the processes effect the oxidation level of the surface. Different catalytic metals can also lead to higher quality graphene. Synthesised graphene can be cleaned from amorphous carbon by treating it with carbon dioxide or changing the carbon precursor for the chemical vapor deposition process. In the experimental part, the effects of higher concentration of hydrogen during synthesis was studied. Higher concentration of hydrogen led to lower nucleation density of graphene, but the catalytic copper surface was damaged in these processes. After synthesis, anneal ing under carbon dioxide flow was studied as a means of cleaning the surface. It was found to reduce amorphous carbon in the product but it increased the manifestation of double layers.